PENGARUH KEPERCAYAAN DIRI, SOFT SKILL DAN DUKUNGAN SOSIAL TERHADAP EMPLOYABILITAS GENERASI Z (Studi Pada Siswa/i SMK Ki Hajar Dewantoro di Tangerang 2024): Fakultas Ekonomi dan Bisnis, Universitas Budi Luhur Jakarta - Fitri, Dewi; Khalid, Zulvia (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2024)
In an increasingly competitive and dynamic job market, having employability is a highly valuable and priceless asset. This study aims to identify several key aspects that can effectively enhance the employability of students at Ki Hajar Dewantoro Vocational School, namely self-confidence, soft skills, and social support. Through an in-depth quantitative analysis of data from 100 randomly selected participants, this study is expected to make a significant contribution to improving the quality of vocational school graduates in facing the ever-changing challenges of the job market. The findings of this study underscore the importance of soft skills and social support in overall student employability. This indicates that efforts to enhance employability should focus more on the development of soft skills and the strengthening of students' social support networks for more optimal results.